The kinetic properties of the glutamate dehydrogenase of Teladorsagia circumcincta and their significance for the lifestyle of the parasite - Noorzaid, Muhamad; Simcock, David C.; Pedley, Kevin C.; Simpson, Heather V.; Brown, Simon (Elsevier Inc., 2011)
Like other nematodes, both L3 and adult Teladosagia circumcincta secrete or excrete NH3/NH4 +, but the reactions involved in the production are unclear. Glutamate dehydrogenase is a significant source NH3/NH4 + in some species, but previous reports indicate that the enzyme is absent from L3 Haemonchus contortus.We show that glutamate dehydrogenase was active in both L3 and adult T. circumcincta. The apparent Kms of the L3 enzyme differed from those of the adult enzyme, the most significant of these being the increase in the Km for NH4 + from 18 mM in L3 to 49 mM in adults. The apparent Vmax of the oxidative deamination reaction was greater than that of the reductive reaction in L3, but this was reversed in adults. The activity of the oxidative reaction of the L3 enzyme was not affected by adenine nucleotides, but that of the reductive reaction was stimulated significantly by either ADP or ATP. The L3 enzyme was more active with NAD+ than it was with NADP+, although the activities supported by NADH and NADPH were similar at saturating concentrations. While the activity of the oxidative reaction was sufficient to account for the NH3/NH4 + efflux we have previously reported, the reductive amination reaction was likely to be more active.